Dynamic slag/refractory interaction of lightweight Al2O3–MgO castable for refining ladle. Issue 6 (July 2015) - Liang, Yonghe; Huang, Ao; Zhu, Xinwei; Gu, Huazhi; Fu, Lvping
Abstract: In order to better understand the dynamic slag/refractory interaction of a lightweight Al2 O3 –MgO castable during steel refining and to avoid the effect of centrifugal force, test bars were immersed in slag at different rotation rates. The results showed that the dissolution was governed by the transport of reaction species of Al2 O3 through the slag at the interface. The corrosion rate of the lightweight Al2 O3 –MgO castable remained almost the same as that of conventional Al2 O3 –MgO castables, regardless of rotation speed. Thus a refining ladle can be fabricated that weighs less and retains the same lifetime as common castables.